Analisis Yuridis Terhadap Instansi Pendidikan Yang Melakukan Penahanan Ijazah Menurut Hukum Perdata - Keppy, Christmas Petra; Adrini, Shaina Subha; Loren, Medina; Ariana, Jessica; Nurdiannisa, Alifa; Yuli, Yuliana (Media Hukum Indonesia (MHI), 2024)
This study examines the practice of withholding diplomas by educational institutions from legal, sociological, and philosophical perspectives. Diploma withholding is often implemented by schools as a means to enforce tuition payment, but this practice raises legal and ethical controversies. This research employs a literature study method with a descriptive-analytical approach to analyze the legal basis for diploma withholding, its impact on students' rights, and its relation to Sustainable Development Goals (SDGs) Number 4 on quality education. The findings indicate that withholding diplomas without clear legal grounds violates students' rights and can negatively affect educational access equality. Diploma withholding also exacerbates social and economic disparities. Therefore, legal advocacy and policy changes are needed to ensure that diploma withholding is conducted in accordance with legal provisions and justice principles.